The Parelsnoer Institute: A National Network of Standardized Clinical Biobanks in the Netherlands. (17th February 2017) - Manniën, Judith; Ledderhof, Tessa; Verspaget, Hein W.; Snijder, Roger R.; Flikkenschild, Erik F.; van Scherrenburg, Nicole P. C.; Stolk, Ronald P.; Zielhuis, Gerhard A.
The Parelsnoer Institute (PSI) is a collaborative biobanking project of all eight University Medical Centers in the Netherlands which was launched in 2007. Basically, PSI consists of three dimensions: participating institutions, disease entities and a central organization. An executive board for operational management instigates collective strategic and tactic policies and a central team of PSI experts and advisors supports the researchers and the board in establishing and implementing standards and procedures. PSI offers researchers an infrastructure and standard procedures for the establishment, expansion and optimisation of clinical biobanks for scientific research. To ensure patient privacy clinical data is pseudomized and carefully stored in a central database. Human biomaterials are collected according to nationally agreed standards. Currently PSI covers fifteen large disease specific cohorts (the so-called 'Parels' or 'Pearls') and new 'Pearls' are being developed. The Parelsnoer Institute currently (December 2016) has stored more than 538, 000 biospecimens with annotated clinical data of more than 30, 000 patients. All these materials and data are available for anyone with a bona fide research proposal.